16S rRNA long-read nanopore sequencing is feasible and reliable for endometrial microbiome analysis. Issue 6 (June 2021) - Oberle, Anna; Urban, Lara; Falch-Leis, Stefanie; Ennemoser, Chiara; Nagai, Yoko; Ashikawa, Kyota; Ulm, Patricia A.; Hengstschläger, Markus; Feichtinger, Michael
Abstract: Research question: Full-length 16S rRNA gene sequencing using nanopore technology is a fast alternative to conventional short-read 16S rRNA gene sequencing with low initial investment costs that has been used for various microbiome studies but has not yet been investigated as an alternative approach for endometrial microbiome analysis. Is in-situ 16S rRNA gene long-read sequencing using portable nanopore sequencing technology feasible and reliable for endometrial microbiome analysis? Design: A prospective experimental study based on 33 patients seeking infertility treatment between January and October 2019. A 16S rRNA gene long-read nanopore sequencing protocol for analysing endometrial microbiome samples was established, including negative controls for contamination evaluation and positive controls for bias evaluation. Contamination caused by kit and exterior sources was identified and excluded from the analysis. Endometrial samples from 33 infertile patients were sequenced using the optimized long-read nanopore sequencing protocol and compared with conventional short-read sequencing carried out by external laboratories. Results: Of the 33 endometrial patient samples, 23 successfully amplified (69.7%) and their microbiome was assessed using nanopore sequencing. Of those 23 samples, 14 (60.9%) were Lactobacillus -dominated (>80% of reads mapping to Lactobacillus ), with 10 samples resulting in more than 90% Lactobacillus reads. Our long-read nanopore sequencing revealed results similar to two conventional short-read sequencing approaches and to long-read sequencing validation carried out in external laboratories. Conclusion: In this pilot study, 16S rRNA gene long-read nanopore sequencing was established to analyse the endometrial microbiome in situ that could be widely applied owing to its cost efficiency and portable character.